AB0217 Biomarkers of Inflammation in Juvenile Idiopathic Arthritis (JIA). (10th June 2014) - Brunner, J.; Giner, T.; Weiss, G.; Fuchs, D.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is a relevant autoimmune disease in children. T cells, B cells, and damage-associated molecular patterns (DAMPS) are involved in the pathogenesis of the disease. Biomarkers for JIA and its subtypes are not established. Pro-inflammatory pathways activate enzyme indoleamine 2, 3-dioxygenase (IDO) which enhances tryptophan (Trp) conversion to kynurenine (Kyn). Thus, in conditions of chronic immune activation reduced Trp availability and production of Kyn and its down-stream metabolites may inhibit cell proliferation. In rheumatoid arthritis (RA) Trp concentrations are lower in patients than in controls and the Kyn/Trp ratios are higher and correlate with neopterin concentrations [1-3]. Objectives: To evaluate Tryptophan as Biomarker in JIA Methods: In this study, Trp and Kyn metabolism was investigated in children with JIA and compared to serum neopterin concentrations. Fifty-four sera of 25 JIA patients and 10 samples of synovial fluid were examined with HPLC (Trp and Kyn) and Elisa (Neopterin, BRAHMS, Hennigsdorf, Germany). Eighteen sera from 18 children with non-inflammatory diseases were used as controls. Results: Trp in the sera of patients was mean 57.2 + SD 19.0 μmol/L and Kyn was mean 2.40 + SD 0.81 μmol/L). Serum neopterin was 5.69 + SD 1.72 nmol/L. In the synovial fluid, neopterin was mean 10.5 + SD 7.41 nmol/L), Trp was 36.7 + SD 17.4 μmol/L and Kyn was 2.13 + SD 0.75 μmol/L). In control patients, neopterin was 6.93 + SD 3.10), Trp was 57.6 + SD 14.8) and Kyn was 2.60 + SD 1.60 μmol/L. Conclusions: Serum Trp concentrations showed no relevant difference in JIA patients vs. controls. IDO activity reduces Trp primarily in the synovial fluid in JIA patients. References: Schroecksnadel K, et al. Increased degradation of tryptophan in blood of patients with rheumatoid arthritis. J Rheumatol 2003;30:1935-9. Fagerer N. et al. Expression of neopterin and chemokines in rheumatoid arthritis and cardiovascular disease. Pteridines 2011;22:7-12. Kurz K, et al. Effects of adalimumab therapy on disease activity and interferon-γ-mediated biochemical pathways in patients with rheumatoid arthritis. Autoimmunity 2011;44:235-42. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4864